Aplikasi Promosi dan Penjualan Business-to-Business Berbasis Web (Studi Kasus PT. Revass Utama Medika) - Nengsiana, Nengsiana; Ayumi, Vina (JSAI (Journal Scientific and Applied Informatics), 2024)
The existence of a sales information system in the current digital era is increasingly important for companies in managing their business processes. The purpose of this research is to analyze the design of a Business-to-Business Promotion and Sales information system so that it makes it easier for companies to integrate information needs that can support overall services and adjust sales and product marketing strategies that are more targeted. The research methods used include field studies and observations by conducting interviews using the waterfall method, modeling design using the UML method. The results of the analysis carried out show that the manual sales information used in this company is inefficient and it is proposed to create a web-based sales and promotion application. The aim of making this application is to improve time efficiency in processing and transactions as well as more targeted product marketing. This application has several quite complete features such as adding and deleting products, a sales graph dashboard, transaction features, shipping options features and sales report retrieval features.